Triplets with growth failure, microcephaly, mental retardation, nail hypoplasia and corpus callosum agenesis: is it a variant of Coffin-Siris or a new syndrome? - Kırel, Birgül; Kural, Nurdan; Yakut, Ayten; Adapınar, Baki (The Turkish Journal of Pediatrics, 2000)
We report eight-year-old triplet girls whose clinical features included microcephaly, severe mental retardation, hypoplasia of distal phalanges of both fifth and second fingers and nail hypoplasia on second fingers, dysmorphic facial features, and partial corpus callosum agenesis. During infancy, a Pavlik harness was used for congenital hip dislocation, and they had difficulty in feeding. One had been operated for patent ductus arteriosus. To our knowledge, this rare combination has not been previously reported in triplets whose clinical features closely resemble those of Coffin-Siris syndrome. The other diagnostic possibilities are also reviewed.